Dichotic delayed auditory feedback in normals and stutterer - Rao, Parimala (Journal of All India Institute of Speech and Hearing)
In the present study, Delayed Auditory Feedback (DAF) speech was used in a dichotic condition. Fifteen normals and fifteen stutterers between the age range 0f 16 to 25 years were taken for the study. All the thirty subjects underwent a preexperimental condition, where they read a ’one minute’ passage in English under Normal Auditory Feedback (NAF) condition to both the ears at 95 dB SPL. The time taken to read the passage, articulatory disturbances and fluency changes were noted down for normals and stutterers. After a rest period of 45 seconds, they were exposed to the II, III and IV experimental conditions.